Analisis Tingkat Literasi Siswa pada Implementasi Kurikulum Darurat pada Masa Pandemi Covid 19 di SD Negeri 03 Mantang - eka rukmana; Moh. Irfan; Zulfadli Hamdi; Muhammad Husni (Lembaga Bale Literasi, 2022)
The purpose of this studt was to determine the level of study reading Literacy in the implementation of the emergency curriculum during the covid-19 pandemic, the method used by the research was a qualitative method. The subjects in this study were grade 3 SD Negeri 03 Mantang. The type of data used in this study was descriptive qualitative data. Data was collected using observation, interviews, and documentation. This study used data analysis techniques for the Miles and Huberman concept, which consisted of data reduction, data presentation, and conclusion drawing. The results obtained from this study were from 20 total students, only 1 student still had difficulty reading. Then there are 5 students in the medium category while the rest are in the category of being able to read well.